Agro-Climatic Bulletin: empowering 221,000 Vietnamese farmers against climate change - Swaans, Cornelis; Le, Tam Thi (2024)
Through Local Technical Agroclimatic Committees (LTACs) and multimedia, timely Agro-Climatic Bulletins (ACB) are being disseminated to over 221,000 farmers in 521 communes in 52 districts in all 13 provinces of Vietnam’s Mekong River Delta (MRD). The Ministry of Agriculture and Rural Development (MARD) recognized the process of ACB development and dissemination as a new Technical Advance and approved the Department of Crop Production’s (DCP) workplan and budget to extend its climate-resilient and preparedness approach to all 13 MRD provinces.